2019
DOI: 10.1108/ijrdm-09-2018-0189
|View full text |Cite
|
Sign up to set email alerts
|

Consumer experience of interactive technology in fashion stores

Abstract: Purpose Despite the growth of digital fashion shopping, many consumers regularly visit physical fashion stores. To enable digital interactions in a physical store, many fashion brands have installed interactive technology. However, studies of consumer engagement with interactive technology in fashion stores remain scarce. The purpose of this paper is to explore the experience with interactive technology in fashion stores. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 66 publications
(83 reference statements)
0
35
0
2
Order By: Relevance
“…The positive performance of technological devices increases store revisit intention (Inman and Nikolova, 2017). Thus, easy in-store use of a mobile phone could positively impact store choice or purchase behaviour within the store Aiolfi, 2017, 2020;de Kerviler et al, 2016b), as it enables consumers to take control of their omnichannel shopping experience (de Haan et al, 2018;Lemon and Verhoef, 2016;Siregar and Kent, 2019). Kowatsch and Maass (2010) also showed that the in-store use of mobile recommendation agents (MRAs) influences product purchases and predicts consumers' usage intention and store preferences.…”
Section: Customers' In-store Smartphone Use and Store Loyaltymentioning
confidence: 99%
See 1 more Smart Citation
“…The positive performance of technological devices increases store revisit intention (Inman and Nikolova, 2017). Thus, easy in-store use of a mobile phone could positively impact store choice or purchase behaviour within the store Aiolfi, 2017, 2020;de Kerviler et al, 2016b), as it enables consumers to take control of their omnichannel shopping experience (de Haan et al, 2018;Lemon and Verhoef, 2016;Siregar and Kent, 2019). Kowatsch and Maass (2010) also showed that the in-store use of mobile recommendation agents (MRAs) influences product purchases and predicts consumers' usage intention and store preferences.…”
Section: Customers' In-store Smartphone Use and Store Loyaltymentioning
confidence: 99%
“…and a sense of belonging as members of the store/retailer's community. Siregar and Kent (2019) have recently underlined the critical role of interactive information and interaction moments. By accessing this mobile app/platform, all actors (consumers and personnel, both in and out of the store) can interact through the real-time exchange of information throughout the store visit, increasing store value and hence store loyalty.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The pervasive, interactive and ubiquitous technology is opening up the debate on how to use ICT to improve the retailer-customer relationship to enhance the shopping experience (Caboni and Hagberg, 2019). The introduction of in-store digital tools such as QR codes, virtual screens, shelves and isles, self-service kiosks, self-scanning machines (Piotrowicz and Cuthbertson, 2014;Siregar and Kent, 2019), as well as the integration of augmented virtual elements (Caboni and Hagberg, 2019;Flavi an et al, 2019), may influence the in-store shopping experience. Likewise, gamification and social cues may enhance the online shopping experience (Insley and Nunan, 2014;Rodrigues et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gamification is gaining more relevance in the literature specifically addressed at studying the usage of interactive technologies to enrich the customer experience (Caboni and Hagberg, 2019;Flavi an et al, 2019;Piotrowicz and Cuthbertson, 2014;Siregar and Kent, 2019). Nevertheless, the marketing literature on the topic is still in its infancy (Hamari et al, 2014) and is lacking of empirical evidence (Hamari, 2013;Hofacker et al, 2016;Tobon et al, 2020), above all considering the variety of marketing domains in which gamification may influence the interaction between the interface and the user.…”
Section: Introductionmentioning
confidence: 99%
“…The perceived interaction within smart retail experiences is related to the overall assessment of smart retail technology and consumer interaction [69]. Moreover, as interactive experiences during technology use evoke the strongest emotions and reactions in users [70], interactive experiences can leave a deep impression on a consumer's memory [71]. Technology-based interactions can increase user interactions with brands and, ultimately, increase customer satisfaction [18].…”
Section: Hypothesis 2d (H2dmentioning
confidence: 99%